2015
DOI: 10.1186/s12889-016-2748-z
|View full text |Cite
|
Sign up to set email alerts
|

Association of household income and education with eating behaviors in Japanese adults: a cross-sectional study

Abstract: BackgroundSocioeconomic inequalities as social determinants of health are important issues in public health and health promotion. However, the association between socioeconomic status and eating behaviors has been investigated poorly in Japanese adults. To fill this gap, the present study examines the association of eating behaviors with household income and education.MethodsThe sample comprised 3,137 Japanese adults (1,580 men and 1,557 women) aged 30 to 59 years who responded to an Internet-based cross-secti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 36 publications
3
31
1
2
Order By: Relevance
“…Participants were randomly selected based on Japanese population statistics for the present study. We targeted adults because of the necessity of health promotion, healthy eating, and reduction in health disparities for this age group [23]. The following inclusion criteria are considered: (1) men and women aged 30–59 years old; (2) able to understand Japanese; (3) can access the Internet at home, work, or a public place; (4) agree to access the study website during the 5-week intervention period; (5) will participate in all three assessment points during the 4-month study period.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Participants were randomly selected based on Japanese population statistics for the present study. We targeted adults because of the necessity of health promotion, healthy eating, and reduction in health disparities for this age group [23]. The following inclusion criteria are considered: (1) men and women aged 30–59 years old; (2) able to understand Japanese; (3) can access the Internet at home, work, or a public place; (4) agree to access the study website during the 5-week intervention period; (5) will participate in all three assessment points during the 4-month study period.…”
Section: Methodsmentioning
confidence: 99%
“…The average daily intake among lower-income social groups is a further 70 g lower than that among higher-income groups. Our nationwide survey of adults on the actual situation regarding the relationship between socio-economic status and dietary habits showed that, lower-income groups are less likely to have a habit of eating five servings of vegetables daily than are higher-income groups [23]. However, even among higher-income groups, the proportion of individuals who customarily consume five servings of vegetables daily is extremely small, at approximately 10% of the population [24].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Finland, individuals with lower annual incomes had lower self-rated health statuses and a higher prevalence of long-standing illnesses (24). Even in Japan, higher household incomes were reported to be associated with better eating habits, such as consumption of more vegetables and more frequent conversations with friends or family during meals (25).…”
Section: Discussionmentioning
confidence: 99%
“…Healthy eating habits are one of the major factors of health promotion and one of the ways to improve public health. Nakamura et al [6] are of the opinion that a higher SES and income are associated with healthy eating habits among men and women. On the other hand, some diseases such as diabetes are more common among the socioeconomic elite.…”
Section: Introductionmentioning
confidence: 99%